«Petites difficultés » de traduction et la volonté de rester francophone en Amérique du Nord - Merkle, Denise (Wydawnictwo Naukowe UAM, 2008)
This article outlines briefly Acadian literary history in New Brunswick from 1970 to the present and concentrates on four writers: A. Maillet (La Sagouiné), R.G. LeBlanc ("Je suis Acadien"), G. Leblanc (Moncton Mantra) and F. Daigle (Petites difficultés d'existence). Their work is marked by the portrayal of sociolinguistic conflict between minority French and dominant English in Canada. We attempt to determine the consequences of this conflict on the translation of the works into English. Each literary presentation is followed by a short analysis of the respective translated passage taken from La Sagouine (L. de Céspedes), "I am Acadian" (F. Cogswell/J.-A. Elder), Moncton Mantra (J.-A. Elder) and Life's Little Difficulties (R. Majzels).
Petites difficulties of translation and the wish to become a francophone in North America
Keywords: Acadian literary history; Francophone